THE CONTRIBUTION OF DJADIDS TO THE DEVELOPMENT OF UZBEK LITERARY LANGUAGE - Berdak Yusufov (Journals Park Publishing, 2024)
The article discusses the role of the Jadids in the development of the Uzbek literary language, their views on the new alphabet, and their services in this field. In particular, initiatives to introduce a new alphabet will be analyzed. The results and importance of these events are shown.
Keywords: Alphabet, Arabic alphabet, Cyrillic alphabet, Jadid, dialect, intelligently, autonomy, Turkestan, language, common Turkic.